AN ASSESSMENT OF INSTITUTIONAL RESTRUCTURING IN REGIONAL POLICY - Feyza Eldeniz (European Regional Science Association (ERSA), 2011)
Regional policy arrangements are extremely complicated and there are various basic constituents for regional economic development such as accession the economic core, competitiveness in leading sector, capital and labour accumulation to be taken hold by regions. As the scope of this paper in overlapping the mentioned issue, one of them is the institutional setting which affects the growth and is rooted in. The aim, therefore, is to examine what extent institutions have an impact on regional policy and the process of formation of institutions within the regional field. As lying at the centre of the study, this academic paper puts forward the argument that institutions have long been neglected in the regional policy action. Then, it is discussed on whether institutions matter development and cause growth or not. Rather now, the attention is turned towards assessing what kind of institutions are to be created for regional development. Subsequently, new emphasis underlies the diversity of institutions and their comprehensive sight comparison to earlier practice. Under the risen argument, firstly; looking at the theoretical discussion in institutions as a major determinant of regional policy, this paper highlights an evolutionary approach by exploring intersection between institution and regional economic development. Secondly, it offers a critical assessment of regional development with reference to paradigm shift in institutional formation. On the basis of this restructuring, the paper concludes by drawing on institutionalized regional framework.
Keywords: 330; institutionalization; institutional setting in regions; regional development